Using Large Linked Field Data Sets to Investigate Density's Impact on the Performance of Washington State Department of Transportation Asphalt Pavements. Issue 9 (September 2021) - Howell, Ryan; Muench, Stephen; Ashtiani, Milad Zokaei; Feracor, James; Russell, Mark; Uhlmeyer, Jeff
Large data sets of Washington State Department of Transportation (WSDOT) pavement construction and condition data are linked together and used to investigate an implemented change in in-place density to lower specification limit (LSL) from 91% to 92%. This serves as a test case for using such large in-service data sets to create analysis value for a state DOT. Findings include: (1) WSDOT field density has remained relatively steady at 93% for over 20 years; (2) raising the density LSL to 92% will likely result in more contractor effort to achieve higher densities; (3) no clear trend links density with better pavement condition; (4) raising the density LSL will likely result in fewer problematically low densities; and (5) there is no evidence of differing pavement performance based on asphalt content, gradation, or nominal maximum aggregate size.